Emergent Marketing Strategies and Performance: The Effects of Market Uncertainty and Strategic Feedback Systems. (18th October 2012) - Chari, Simos; Katsikeas, Constantine S.; Balabanis, George; Robson, Matthew J.
<x xml:space="preserve">Abstract</x> Although many process‐based studies appear in the strategic management literature, little attention has been devoted to the formation process of marketing strategies. Drawing on enactment and information‐processing theories, this study views the external environment as a source of information (i.e. enacted) and organizations as information‐processing entities. We propose a conceptual framework of antecedents and market performance consequences of emergent marketing strategies and test it with a sample of 214 UK enterprises. The results suggest that dimensions of market uncertainty (i.e. dynamism and complexity) and strategic feedback systems influence the formation of emergent marketing strategy. Furthermore, the data reveal that market uncertainty aspects condition the association between emergent marketing strategies and market performance in different ways. These findings provide new insights into how emergent marketing strategies evolve and influence organizational outcomes.